Work–family conflict, affective commitment, leadership and job satisfaction: a moderated mediation analysis. Issue 4 (26th January 2021) - Panda, Abinash; Jain, Nikunj Kumar; Nambudiri, Ranjeet
Abstract : Purpose: The detrimental influence of perceived work–family conflict (WFC) on employees' job-related attitudes has been examined in individualistic cultures. However, this relationship needs to be studied in collectivist societies, where the "family" is a salient social institution with family-centric work ethics. This study empirically investigates the role of nurturant task leadership (NTL) behavior in attenuating (1) the negative direct effect of perceived WFC on job satisfaction and (2) the negative indirect effect of perceived WFC on job satisfaction, mediated through affective commitment (AC) on a sample of employees from a public sector bank in India. Design/methodology/approach: The study adopts a cross-sectional research design, and the data were collected from 244 executives working in the banking sector of India. The direct, indirect and moderated effects were analyzed using ordinary least squares (OLS) regression. Findings: NTL behavior was found to moderate the negative direct relationships between perceived WFC and job satisfaction as well as the negative indirect relationship between perceived WFC and job satisfaction, mediated through AC. Research limitations/implications: The study contributes to existing literature on WFC by introducing an important boundary condition in NTL behavior, thus providing impetus to further research in this direction through research designs that allow for causal inference and generalizability. Practical implications: Findings from this study can provide useful pointers to organizations dealing with employee performance challenges owing to WFC. Results indicate that leaders who exhibit NTL behavior are more likely to attenuate the negative influence of WFC on employee attitudes and performance. Originality/value: This study is among the first empirical examination of the effectiveness of NTL behavior in mitigating the negative effects of perceived WFC on job satisfaction.